2006
DOI: 10.1385/bter:114:1:293
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Toxic Mechanism of La<sup>3+</sup> to Escherichia coli

Abstract: The toxic mechanism of La3+ to Escherichia coli is investigated by detecting the concentration change of La3+ in E. coli cells growing in La3+-containing medium. Stimulatory action and inhibitory effect of La3+ in different concentrations can be attributed to the permeability alteration of the cell. Low concentration of La3+ increases the nutrition absorbability of the cells from the cultures as a result of increased cell permeability, and high concentration of La3+ causes the accumulation of La3+ in cells, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In the presence of tourmaline, the cell permeability is slightly increased, and the absorbability of nutrition from the medium becomes easier. As a result, N. europaea grows faster in the presence of tourmaline than the native cells, in agreement with previous conclusion that the increase of cell permeability enhanced the nutrition absorbability of bacterial …”
Section: Resultssupporting
confidence: 92%
“…In the presence of tourmaline, the cell permeability is slightly increased, and the absorbability of nutrition from the medium becomes easier. As a result, N. europaea grows faster in the presence of tourmaline than the native cells, in agreement with previous conclusion that the increase of cell permeability enhanced the nutrition absorbability of bacterial …”
Section: Resultssupporting
confidence: 92%
“…A low concentration of La 3+ increased the nutrient absorbance of the cells due to increased cell permeability. A high concentration of La 3+ increased the accumulation inside the cell, causing a toxic effect on the cell, hence, exhibiting stimulatory and inhibitory effects on the E. coli cells [99].…”
Section: Ecotoxicity Of Lanthanum (La)mentioning
confidence: 99%
“…Zhang et al. () and Peng, Hongyu, Xi, Chaocan, and Yi () reported that the low concentration of, down to 4 × 10 −4 mol/L, lanthanum cation increased the nutritional uptake of E . coli cells and did not produce any toxic effect.…”
Section: Introductionmentioning
confidence: 99%